2022
DOI: 10.1017/ash.2022.242
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative approach to examining antimicrobial prescribing in the outpatient dental setting

Abstract: Objective: To understand barriers and facilitators to evidence-based prescribing of antibiotics in the outpatient dental setting. Design: Semistructured interviews. Setting: Outpatient dental setting. Participants: Dentists from 40 Veterans’ Health Administration (VA) facilities across the United States. Methods: Dentists were identified based on their prescribing patterns and were recruited to participate in a semistructured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Two studies identified that dentists were motivated to prescribe due to concerns of conflict, in which they fail to meet their patients' expectations (20,23). Additionally, research has identified conflict avoidance was a method to maintain a good clinician-patient relationship in dental practices (21). Patient satisfaction and financial stability is particularly a concern for dentists because nearly 50% of dentists work in solo practices (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies identified that dentists were motivated to prescribe due to concerns of conflict, in which they fail to meet their patients' expectations (20,23). Additionally, research has identified conflict avoidance was a method to maintain a good clinician-patient relationship in dental practices (21). Patient satisfaction and financial stability is particularly a concern for dentists because nearly 50% of dentists work in solo practices (37).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Thompson et al identified that though dentists were aware of risks, some viewed the risk of antibiotic‐associated adverse events as less than the risk of a spreading dental infection. Furthermore, a qualitative study of dentists recruited from high‐and‐low prescribing Veterans Health Administration (VHA) facilities found that dentists at high prescribing facilities displayed a lack of awareness of the harm of their prescribing (21). Whereas dentists in low‐prescribing sites displayed more awareness of: (1) potential antibiotic‐associated harms and (2) ongoing initiatives to improve prescribing at their VHA facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Manning et al 16 demonstrated how patient simulations can improve nursing-student awareness of their role in antimicrobial stewardship. Hughes et al 17 identified several opportunities for improvement in dental antimicrobial stewardship, including improved awareness of and access to evidence-based guidelines, as well as harnessing social comparison to improve prescribing behavior.…”
Section: Think Beyond the Hospital Walls And Beyond The Prescribermentioning
confidence: 99%
“…In a cross-sectional study using interviews of 90 dentists, 91.2% stated that they prescribed on a 'just in case' basis. 17 In a retrospective cohort study, 205 patients (80.7%) received empiric antibiotic therapy indicated for presumed urinary tract infection despite meeting criteria for asymptomatic bacteriuria. 18 However, given the known harms of antibiotic therapy, there is an opportunity to reframe messaging regarding "erring on the side of caution" to now mean thoroughly evaluating and monitoring the patient while considering other noninfectious causes before prescribing an antibiotic.…”
Section: Reframe What the "Safe Side" Ismentioning
confidence: 99%